MARKETING COMMUNICATION, E-WOM, AND TOURISM EVENTS IN SHAPING VISIT INTENTION: THE MEDIATING ROLE OF DESTINATION IMAGE - Futri Rezki Indah; Yacob, Syahmardi; Musnaini (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
Abstract This study examines the role of destination image as a mediating variable in the relationship between marketing communication, electronic word of mouth (e-WOM), tourism events, and visiting intention in Tanjung Jabung Timur Regency, Indonesia. Tourism development in the region has shown fluctuating growth, indicating the need for more effective strategic marketing efforts. Grounded in the Stimulus-Organism-Response (S-O-R) framework and the Theory of Planned Behavior (TPB), this research proposes that destination image functions as a psychological mechanism linking marketing stimuli to behavioral intention. A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through structured questionnaires distributed to respondents aged 17 years and above who had accessed tourism-related information about Tanjung Jabung Timur. The findings reveal that marketing communication, e-WOM, and tourism events significantly influence visiting intention. Tourism events demonstrate the strongest direct effect on visiting intention, while e-WOM has the strongest influence on destination image. Furthermore, destination image significantly affects visiting intention and mediates the relationship between marketing communication and visiting intention, as well as between e-WOM and visiting intention. However, destination image does not mediate the relationship between tourism events and visiting intention. The model shows strong explanatory power, highlighting the importance of integrated digital marketing strategies and online engagement in strengthening destination image and enhancing tourism competitiveness in Tanjung Jabung Timur Regency.